PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TRUE OR FALSE TERHADAP HASIL BELAJAR PPKN SISWA KELAS VIII SMP NEGERI 2 SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Desti Atma Wijaya; Sri Erlinda; Gimin Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the low learning result of PPKn students in SMP Negeri 2 Sentajo Raya Kuantan Singingi Regency. The formulation of the problem in this research is: "Is there any influence of Kooperati model model true or false type to the learning result of Vocational High School student of VIII SMP Negeri 2 Sentajo Raya Kuantan Singingi Regency?". This study aims to determine the effect of true or false learning model on student learning outcomes in learning PPKn in SMP Negeri 2 Sentajo Raya Kuantan Singingi regency in January 2017. This research is a quantitative descriptive study that became population in this study are students of class VIII SMP Negeri 2 Semtajo Raya Kuantan Singingi Regency. The sample in this research is class VIII C as the control class of the students who were given the lecture method and the class VIII A as the experimental class students who were given the learning model true or false then the data were analyzed using homogeneity test and t test. Based on the results of the research indicates that there is a positive effect on the learning outcomes of students who applied the learning model true or false than using conventional methods in SMP Negeri 2 Sentajo Raya with the price (t_hitung 7.56 => t_tabel = 2.00). Thus obtained the hypothesis that there is a significant positive influence between the application of the model true or false with the results of student learning class VIII A SMP Negeri 2 Sentajo Raya Kuantan Singingi district is acceptable.Keywords: True or False, and Learning Outcomes